Board Informal Hierarchy and Firm Financial Performance: Exploring a Tacit Structure Guiding Boardroom Interactions - He, Jinyu; Huang, Zhi (Academy of Management Journal, 2011)
We consider boards as human groups in the uppermost echelon of corporations and examine how an informal hierarchy that tacitly forms among a firm's directors affects firm financial performance. This informal hierarchy is based on directors' deference for one another. We argue that the clarity of the informal hierarchy can help coordinate boardroom interactions and thereby improve the likelihood of the board's contributing productively to the firm's performance. We further identify a set of internal and external contingencies affecting the functioning of the informal hierarchy. Our analysis of seven-year panel data on 530 U.S. manufacturing firms provides support for our arguments.